The life of Buddhism - Reynolds, Frank E.; Carbine, Jason A. (The life of religion, 2000)
Bringing together fifteen essays by outstanding Buddhist scholars from Asia, Europe, and North America, this book offers a distinctive portrayal of the "life of Buddhism." The contributors focus on a number of religious practices across the Buddhist world, from Sri Lanka to New York, Japan to Tibet